MENINGKATKAN KEMAMPUAN MENGENAL WARNA MELALUI KEGIATAN MENCOCOKKAN WARNA DENGAN BALOK WARNA PADA ANAK USIA 3-4 TAHUN DI KB QURROTU AINI KOTA ANYAR PROBOLINGGO - Rufikyanti; kharismawati, Indah; Suwargono, Trio (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to recognize colors is an important aspect of cognitive development in early childhood. Initial observations indicated that most children in Group A aged 3–4 years were not yet able to distinguish and name colors correctly. This study aimed to improve children’s color recognition ability through color-matching activities using colored blocks.The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The research subjects were 20 children in Group A aged 3–4 years. A mixed-methods approach was applied, combining qualitative and quantitative methods. Qualitative data were collected through observations, interviews, and documentation, while quantitative data were obtained from assessments of children’s developmental achievements.The results showed a significant improvement in children’s color recognition ability, increasing from 40% in the pre-cycle to 65% in Cycle I, and reaching 90% in Cycle II. Therefore, color-matching activities using colored blocks were proven to be effective in enhancing color recognition abilities in children aged 3–4 years.